WOMEN'S AGRICULTURAL PRODUCTION IN GUINEA-BISSAU AS A MEANS OF STRENGTHENING THEIR IDENTITY - Carlos Sangreman; Mara Melo (Ars Educandi)
This article was developed from the study done for the Swiss Cooperation in Guinea-Bissau on women horticulturists. The data were obtained by surveys and interviews in the regions of Bissau, Biombo, Bafatá and Oio, with the producers (which also include a limited number of male producers) of leguminous agricultural products, in a sample of 160/1063 people chosen at random. To better understand the results, it must be said that this business model is not very profitable, but it is an activity that gives a greater independence of women in relation to men in the family space, combating the existing male authoritarianism, since decisions about the use of profits belong to the women producers. It also has a potential environment of action for the affirmation of the social (and not just family) identity of women that should not be despised although, as far as we can see, this is expressed for now only in the organization of associations of producers. The data matrix and the qualitative observations file are the property of SWISSAID, but the tables obtained from it can be provided to researchers who request them.